A SYSTEMIC FAMILY APPROACH IN WORKING WITH CHILD VICTIMS OF VIOLENCE (Annual of the Faculty of Philosophy in Skopje, 2023)
This paper presents a case study that explores the application of systemic family therapy in working with children who are victims of violence within their family. The case study focuses on the Johnson family, comprising a father, mother, and their two children, who sought therapy after a traumatic incident of domestic violence. The therapeutic approach utilized a systemic family therapy framework, aiming to address the complex dynamics resulting from the violence and its impact on family members. The goals include providing a safe environment for children to process their experiences, enhancing communication, promoting non-violent parenting, and strengthening the family’s support network. The interventions involved individual sessions with the children, family sessions, psychoeducation, and collaborative goal setting. Throughout the therapy process, significant improvements were observed, including enhanced communication, improved emotional well-being for the children, non-violent parenting strategies, and the development of a support network. The findings of this case study highlight the effectiveness of systemic family therapy in promoting healing, fostering healthy relationships, and creating a nurturing environment for children affected by family violence.